Myopathy with mitochondrial inclusion bodies: histological and metabolic studies. Issue 11 (November 1974) - Sulaiman, W. R.; Doyle, D.; Johnson, R. H.; Jennett, S.
Abstract : Apparently new information about a metabolic abnormality has been obtained by measuring biochemical and respiratory responses to controlled exercise in a patient with abnormal mitochondria in muscle fibres. A male patient (49 years old) presented with bilateral ptosis of 15 to 20 years' duration and weakness for one to two years. Biopsies from the deltoid and triceps muscles were subjected to histological, histochemical, and electron microscopical examination. Routine histology showed only minor changes; 2-5% of muscle fibres had pale borders in which there were aggregates of mitochondria and 1-5% of fibres showed atrophy. Histochemical examination showed increased activity of succinic dehydrogenase in mitochondria and lactate dehydrogenase in cytoplasm. Electron microscopy showed crystalline inclusions in many subsarcolemmal mitochondria. Metabolites were studied during and after exercise on an ergometer and revealed remarkable differences from normal. Blood lactate rose to 12·5 μmol/ml and pyruvate to 0·39 μmol/ml compared with up to 4·0 and 0·16 μmol/ml respectively in controls exercising to a comparable percentage of capacity. Concentrations of ketone-bodies and free fatty acids fell during and after exercise, while they rose in the controls. These observations imply a major mitochondrial defect which causes dramatic biochemical changes in fuel supply in blood during exercise. The changes suggest that fat metabolism was accelerated (in this patient) and was related to a block of carbohydrate utilization as fuel.